PENGARUH KUALITAS PRODUK DAN KUALITAS PELAYANAN TERHADAP KEPUASAN PELANGGAN MOBILE BROADBAND DI KOTA PALEMBANG - Hendrianto Hendrianto; Diah Natalisa; Dian Eka (Jurnal Keuangan dan Bisnis, 2018)
This study aimed to analyze product quality and service quality on customer satisfaction.Respondents were the customer of mobile broadband product in Palembang city. Both primary and secondary data were gathered. Secondary data were gathered from various sources such as journals, books and other related publications. Primary data were gathered using questionnaire which were distributed to the respondents. This research used a random sampling technique, a total sample of 100 respondents were obtained. Various statistical analysis tests such as validity, reliability and classical assumption tests were employed. Using a multiple linier regression analysis, the result indicated thatproduct quality and service quality had positive and significant effect on customer satisfaction. The mobile broadband company is suggested to evaluate about the price, product quality, and service quality to provide costumer satisfaction.